2021
DOI: 10.1200/jco.21.00807
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Plus Venetoclax for First-Line Treatment of Chronic Lymphocytic Leukemia: Primary Analysis Results From the Minimal Residual Disease Cohort of the Randomized Phase II CAPTIVATE Study

Abstract: PURPOSE CAPTIVATE ( NCT02910583 ), a randomized phase II study, evaluates minimal residual disease (MRD)-guided treatment discontinuation following completion of first-line ibrutinib plus venetoclax treatment in patients with chronic lymphocytic leukemia (CLL). METHODS Previously untreated CLL patients age < 70 years received three cycles of ibrutinib and then 12 cycles of combined ibrutinib plus venetoclax. Patients in the MRD cohort who met the stringent random assignment criteria for confirmed undetectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
168
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(190 citation statements)
references
References 36 publications
20
168
0
2
Order By: Relevance
“…While the investigated cohort was relatively small ( n = 13), this finding suggests that MEK/Bcl‐2 inhibition is of relevance to both low‐ and high‐risk CLL. This is in agreement with results from the Phase II CAPTIVATE study (NCT02910583), where CLL patients received frontline treatment with the targeted therapies venetoclax plus the BTK inhibitor ibrutinib [ 40 ]. In this study, high undetectable minimal residual disease (uMRD) was observed across patient subgroups, including those with high‐risk disease features [ 40 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While the investigated cohort was relatively small ( n = 13), this finding suggests that MEK/Bcl‐2 inhibition is of relevance to both low‐ and high‐risk CLL. This is in agreement with results from the Phase II CAPTIVATE study (NCT02910583), where CLL patients received frontline treatment with the targeted therapies venetoclax plus the BTK inhibitor ibrutinib [ 40 ]. In this study, high undetectable minimal residual disease (uMRD) was observed across patient subgroups, including those with high‐risk disease features [ 40 ].…”
Section: Discussionsupporting
confidence: 88%
“…This is in agreement with results from the Phase II CAPTIVATE study (NCT02910583), where CLL patients received frontline treatment with the targeted therapies venetoclax plus the BTK inhibitor ibrutinib [ 40 ]. In this study, high undetectable minimal residual disease (uMRD) was observed across patient subgroups, including those with high‐risk disease features [ 40 ]. Clinical data on MEK/Bcl‐2 inhibition in CLL are needed to determine in what setting this combination may be used.…”
Section: Discussionsupporting
confidence: 88%
“…Another strategy that is receiving considerable attention in CLL/SLL (in both R/R and treatment-naïve patient settings) is combination therapy involving a BTK inhibitor and venetoclax (± an anti-CD20 mAb). Currently available data from phase II trials show that treatment with ibrutinib [ 85 89 ], acalabrutinib [ 90 ] or zanubrutinib [ 91 ] in combination with venetoclax (with [ 88 , 90 , 91 ] or without [ 85 89 , 91 ] obinutuzumab) can produce deep responses, with good proportions (38–75% across trials) of patients achieving undetectable MRD. Several phase III trials investigating combinations of a BTK inhibitor and venetoclax (± obinutuzumab or rituximab) are underway (including with fixed-duration regimens), and results will be of particular interest.…”
Section: Therapeutic Efficacy Of Btk Inhibitorsmentioning
confidence: 99%
“…3 ). However, given the potential for ongoing tolerability issues (as well as other factors, including cost), it has been raised whether fixed-duration (or response driven) BTK inhibitor treatment regimens could have an improved risk:benefit ratio [ 81 , 88 , 89 ]. Although deep responses allowing drug discontinuation are generally not rapidly achieved with BTK inhibitor monotherapy, combination therapies (e.g.…”
Section: Current Clinical Position Of Btk Inhibitors In B-cell Malignanciesmentioning
confidence: 99%
“…Conversely, recent frontline data from the CAPTIVATE study demonstrate a similar BM MRD-negative rate of 66% with dual ibrutinib and venetoclax in del(17p)/TP53-mutated CLL. 9 Whether triplet therapy is indeed superior to treatment with dual-or single-targeted agents needs to be determined within prospective randomized studies.…”
mentioning
confidence: 99%